Exposure to particulate matter and ozone of outdoor origin in Singapore - Chen, Ailu (2015)
Estimates of population exposure to ambient air pollution traditionally rely on concentrations measured at central-site monitors as a surrogate for concentrations to which people are exposed. In this study of Singapore, we estimate population-averaged exposure concentrations for PM2.5, PM10, and O3 by applying a model and data that account for age and gender demographics, intraurban regional variability, and microenvironmental effects with age- and gender-stratified time-activity budgets. The study addresses exposure only to air pollutants of outdoor origin. Spatially averaged midpoint estimates of lifetime ambient exposure concentrations are 59%, 52%, and 47% of outdoor concentrations for PM2.5, PM10, and O3, respectively. Utilizing ambient data for calendar year 2007, we estimate that intraurban variability in ambient concentration results in lifetime-integrated exposure concentrations in the respective ranges of 10-14μgm-3 for PM2.5, 14-18μgm-3 for PM10, and 7.5-15μgm-3 for O3. Uncertainty in estimates of the indoor proportion of outdoor pollutants, which are input to the model, results in greater variability than do intraurban differences in ambient concentrations, resulting in respective ranges of 6.6-15μgm-3 for PM2.5, 8.1-21μgm-3 for PM10 and 6.8-16μgm-3 for O3. Estimates of time spent in naturally ventilated (NV) homes are in the range 10-13h/d across the population and exposures in NV homes contribute 49%, 53%, and 56% of total exposure for PM2.5, PM10 and O3, of outdoor origin, respectively. Results illustrate the importance of accurately characterizing climate-specific indoor-outdoor pollutant relationships to better quantify human exposure to air pollutants.